PENGARUH CEKAMAN SALINITAS GARAM NaCl TERHADAP PERTUMBUHAN KACANG TUNGGAK (Vigna unguiculata L. Walp) PADA TANAH GAMBUT - Junandi, Junandi; Mukarlina, Mukarlina; Linda, Riza (Universitas Tanjungpura, 2019)
Vigna unguiculata L. Walp is one of the cultivated plants in West Borneo, usually cultivated on dry land in the dry season and can live on land that is affected by sea water intrusion. High salt levels in the soil can cause crop growth disorders. The purpose of this study was to determine the growth response of cowpea (Vigna unguiculata L. Walp) to the stress of salinity of NaCl. The study was carried out from 2019 to June 2019. Research was carried out using a Completely Randomized Design (CRD), which consisted of four treatments namely 0 ppm, 2500 ppm, 5000 ppm and 7500 ppm. The results showed a significant effect on the parameters of plant height, root length, number of leaves and wet weight, but no significant effect on the parameters of dry weight, root nodules and effective nodules.